Differences in options investors’ expectations and the cross-section of stock returns - Andreou, Panayiotis; Kagkadis, Anastasios; Philip, Dennis; Tuneshev, Ruslan (My University, 2018)
We provide strong evidence that the dispersion of individual stock options trading volume across moneynesses (IDISP) contains valuable information about future stock returns. Stocks with high IDISP consistently underperform those with low IDISP by more than 1% per month. In line with the idea that IDISP reflects dispersion in investors’ beliefs, we find that the negative IDISP-return relationship is particularly pronounced around earnings announcements, in high sentiment periods and among stocks that exhibit relatively high short-selling impediments. Moreover, the IDISP effect is highly persistent and robustly distinct from the effects of a large array of previously documented cross-sectional return predictors.
Keywords: Dispersion of beliefs; Disagreement in options market; Cross-section of stock returns; Equity options; Option trading volume